Pengaruh Harga Dan Gaya Hidup Terhadap Keputusan Pembelian Pakaian Second Import Di Pasar Lemabang Palembang - Muhammad Qori Musyaffa; Iceu sri gustina; Syamsiar Zahrani (Jurnal Ekonomi dan Bisnis Digital, 2022)
This study aims to determine the effect of price and lifestyle on purchasing decisions for second imported clothing in the Lemabang market, Palembang. As for the problem in this study "How do prices and lifestyle influence the decision to purchase Second Import clothing at the Palembang Lemabang market. The sampling technique used the hair technique at al with a total of 72 respondents who were consumers of second-imported clothing in the Palembang Lemabang market. In this study, research data were collected by distributing questionnaires to consumers who had purchased second-hand imported clothing at the Palembang Lemabang Market. The type of data used is primary with data analysis techniques using the SPSS program. The results showed that price has a significant effect on purchasing decisions with a t-count value on the price variable of 4.404 > 1.994 and a significant value of 0.000 <0.05. And also lifestyle has a significant effect on purchasing decisions with a t-count value on lifestyle variables of 2.327 > 1.994 and a significant value of 0.023 <0.05. 77 > from the ftable of 3.13. And a significant value of 0.000 <0.05